Separation of Chemical Elements from Liquid Medium with the Electrochemical Processes on Asymmetric Current; AIP Conference Proceedings; Vol. 2101 : Isotopes: Technologies, Materials and Application (ITMA-2018) - Li H. Hongda; Sosnovskiy S. Sergey; Kazaryan M. Mishik; Sachkov V. Viktor; Abdiyanov A. Almas; Golovkov N. V. Nikita Viktorovich (2019, 2019)
Title screen